Integrasi Pembelajaran Digital Melalui Pengembangan Buku Digital Berbantuan Heyzine pada Materi Geometri di Sekolah Dasar - Nabilah Mansur; Salsa Nabila (Institut Agama Islam Negeri Fattahul Muluk Papua, 2026)
The integration of digital learning in elementary schools has become an effort to support learning processes that are more interactive, contextual, and aligned with technological advancements. This study aimed to describe the development process and determine the validity and practicality of a Heyzine-assisted digital book on geometry materials in elementary school. The study employed the Research and Development (R&D) method using the ADDIE development model implemented through the Analyze, Design, Development, and Implementation stages. Data were collected through observation, interviews, questionnaires, and documentation. Product validation was conducted by material experts, design experts, and learning practitioners. The results showed that the developed digital book achieved a very high level of validity, with material expert assessment reaching 93.75%, design expert assessment reaching 97%, and learning practitioner assessment reaching 96.25%. The practicality test results also indicated a very practical category, with individual trials obtaining 95.24%, small-group trials 97.61%, and large-group trials 98.41%. Based on these findings, the Heyzine-assisted digital book was considered highly valid and highly practical, making it suitable to support the integration of digital learning in geometry instruction at the elementary school level.